К проблеме психического здоровья личности и современного информационного воздействия - Лефтеров, Василь Олександрович; Лефтеров, В. О.; Лефтеров, Василий Александрович; Lefterov, Vasyl O. (Одеса : Південноукраїнський національний педагогічний університет ім. К. Д. Ушинського, 2014)
Статья посвящена теоретико-прикладным аспектам взаимосвязи психического здоровья и информационного воздействия. Рассматриваются понятия психического и психологического здоровья личности, факторы и современное состояние психического здоровья украинцев. Анализируются некоторые психологические механизмы и технологии информационных манипуляций, особенности восприятия и психологические реакции человека на негативное информационное воздействие. Предлагаются концептуальные линии поведения человека для профилактики психического здоровья в условиях негативизации информационного пространства, обосновывается необходимость обеспечения психологической экологичности информации и деятельности СМИ

Стаття присвячена теоретико-прикладним аспектам взаємозв'язку психічного здоров'я та інформаційного впливу. Розглядаються поняття психічного та психологічного здоров'я особистості, фактори і сучасний стан психічного здоров'я українців. Аналізуються деякі психологічні механізми і технології інформаційних маніпуляцій, особливості сприйняття і психологічні реакції людини на негативний інформаційний вплив. Пропонуються концептуальні лінії поведінки людини для профілактики психічного здоров'я в умовах негативізації інформаційного простору, обґрунтовується необхідність забезпечення психологічної екологічності інформації та діяльності ЗМІ.

The article is devoted to theoretical and applied aspects of the interconnection of mental health and the impact of the information. The concepts of mental and psychological health of a personality, factors and the current state of mental health of Ukrainians are considered. Among the factors that negatively affect the mental and psychological health of people the author distinguishes the following: chronic fatigue, fear of loneliness, fears about health, stresses, conflicts, diseases, death of relatives and so on. The total impact on the psychological health and growing threats on a global scale are caused by the following factors: technological disasters, natural disasters, possibility of wars etc. And nowadays, due to the politicization of society, informational impact is a significant factor affecting the mental health of people. The author analyzed some psychological mechanisms and technologies of informational manipulation, perception and psychological characteristics the human response to negative informational influence. It is also substantiated that the direction, intensity, volume and strength of direct and indirect impact of the information forms subjective perception of what is happening, a sense of psychological comfort or discomfort, and correlates with the level of mental and psychological health. The author discusses the need of ensuring psychological ecological compatibility of information and activity of mass media. To counter the negative effects of the information impact the author suggests the following: 1) to manage and rationalize. 2) to minimize the harm of information effects on the psyche and human health – controlled watching TV and online videos, because information impact reduces the potential of the quality of human life. 3) to get positive experience of informational influence. Problems of psychological health and psychological informational ecology can be solved only with the usage of the complex approach, creating and implementing efficient system of acts and events at the public and state level
Лефтеров В. А. К проблеме психического здоровья личности и современного информационного воздействия / В. А. Лефтеров // Наука і освіта. - № 12. - Одеса : Південноукраїнський національний педагогічний університет ім. К. Д. Ушинського, 2014. – С. 177-184.
Keywords: психическое здоровье; информационное воздействие; информационное пространство; психологическая экологичность информации и деятельности СМИ; психічне здоров'я; інформаційний вплив; інформаційний простір; психологічна екологічність інформації та діяльності ЗМІ; mental health; informational impact; information space; psychological ecological compatibility of information and activity of mass media; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology